Astringency sub‐qualities of red wines and the influence of wine–saliva aggregates. (16th May 2021) - Brossard, Natalia; Gonzalez‐Muñoz, Beatriz; Pavez, Carolina; Ricci, Arianna; Wang, Xinmiao; Osorio, Fernando; Bordeu, Edmundo; Paola Parpinello, Giuseppina; Chen, Jianshe
Summary: Astringency is a sensory attribute, related to the quality and mouthfeel of red wines. However, the origin of astringency sub‐qualities, such as the typical drying astringency found in immature grapes, is still unknown. Astringency of red wines with similar tannin content but different astringency sub‐qualities, from different harvest dates, is studied. Astringency was characterised in terms of friction coefficient, polyphenol content, sensory analysis and tannin/salivary–proteins aggregates characterisation. A different evolution during ripening was found for both Cabernet Sauvignon and Carménère, and tannin–protein aggregates showed differences in size, shape and surface. The velvety sub‐quality appears to be related to aggregates with low precipitation, and with specific surface characteristics as roundness and Feret diameter. Results from this work propose an effect of aggregates on sensory perception and opens the possibility to explore their effect on oral lubrication. Abstract : Wine tannins and saliva protein interactions, and the role of its aggregates on astringency perception. ​